A Novel Robust Digital Subarray Partition Algorithm with Binary Coding - Zhao, Yang; Wu, Jianxin; Zhang, Lei (IEEE transactions on antennas and propagation, 2023)
In large-scaled phased array radar signal processing, digital subarray partition technique would reduce the system size and computational complexity effectively. However, increasing inter-subarray spacing will lead to the grating-lobes which degrading the beamforming performance. In this communication, by merging the concepts of encoding technology and subarray division, a novel digital subarray structure based on binary coding is proposed to suppress the grating-lobes and lower the side-lobe level. The core of the algorithm is optimally accommodating the binary coding so that the array is divided into multiple layers of subarrays, including uniform and interleaved structures with various inter-subarray spacing. Thus, the diversity of subarray phase centers is guaranteed and the periodicity of the phase centers is broken. Simulation results are given to demonstrate the superiorities of proposed algorithm in beamforming and efficiency performance.